B Pengembangan Diri Mahasiswa Kesehatan Dalam Menghadapi Perkembangan Teknologi Komunikasi Era 4.0 - Ake Royke Calvin Langingi; Mareyke Y. L. Sepang; Cicilia K. Lariwu; Christiane Sarayar; Chintami L. Watak; Gita Karouw; Prisilia M. Toreh; Zefania I. Pagayang (Cv. Utility Project Solution, 2023)
It is proven that the development of communication technology can change the pattern of communication in human life. However, humans should not be governed by technology, but humans are essentially the regulators of technology. The problem is where is the human position in the development of communication technology. Health students need to understand this concept so they don't get caught up in the development of communication technology in the 4.0 era. The purpose of this Community Service activity is to explain to students the importance of self-development in dealing with developments in communication technology in the 4.0 era. The method used is an interactive lecture method and direct question and answer for students. The result of providing this education is an increased understanding of the importance of self-development in dealing with developments in communication technology in the 4.0 era. Self-development in question is self-adjustment to a position as a consumer in communicating, such as the benefits of the internet, the benefits of smartphones, television and so on. The result of this activity is the need for counseling and training on the transformation of self-development to be better on an ongoing basis from the institution, especially so that it has a positive impact on students and institutions.